Outcomes of liver transplantation in the era of modern antiviral therapy for hepatitis C - K. Yu. Kokina; Yu. O. Malinovskaya; Ya. G. Moysyuk (Вестник трансплантологии и искусственных органов)
The emergence of direct-acting antivirals (DAAs) has become the basis for a new potential treatment for chronic hepatitis C (CHC) in patients with decompensated cirrhosis, who previously had no other alternative than liver transplantation (LT). However, optimal timing of antiviral therapy (AVT) remains an issue. Objective: to present a spectrum of clinical outcomes in LT waitlisted patients with HCV-related cirrhosis, who received and did not receive DAA therapy. Materials and methods. Enrolled for the study were 49 waitlisted patients with HCV-related end-stage liver diseases. The patients were divided into 2 groups: Group 1 included 40 patients who received DAA therapy before LT, while Group 2 consisted of 9 patients who did not receive antiviral treatment while on the LT waiting list. Results. The sample was represented in most cases by patients who had MELD/Na score <20. Only six had MELD/Na score >20, but <25. At the time of analysis, 38 patients had reached 12 weeks post AVT. Of these, 35 (92.1%) had sustained virologic response (SVR). Of these, 51.4% (n = 18) of cases showed decreased MELD/Na. There were no changes in 22.9% (n = 8). Increased MELD/Na was noted in 25.7% (n = 9). In 42.8% (n = 15) of cases, sustained elimination of HCV infection led to delisting. Among patients without SVR, increased MELD/Na was observed in all cases (n = 3). In the non-AVT group, one patient showed improved liver function (11.1%); in the rest, MELD/Na either remained stable or continued to increase - 44.5% (n = 4). A comparison of the frequency of deaths depending on AVT showed statistically significant differences (p < 0.001, V = 0.728). Among the non-AVT patients, the likelihood of waitlist death increased 66.5 times (95% CI: 7.99-554). Conclusion: DAA therapy carries significant advantages for waitlisted patients with MELD/Na score <25.